2021
DOI: 10.52312/jdrs.2021.290
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic asymmetrical bilateral hip dislocation: A rare case report

Abstract: Traumatic bilateral hip dislocation is a rare phenomenon. Simultaneous traumatic asymmetrical bilateral hip dislocation is even more unusual. There is no report in the literature regarding the mechanism of injury in tramcar squeezing. A 49-year-old male who had a serious tramcar accident and developed asymmetric bilateral hip dislocations (left posterior, right anterior) combined with fracture of left acetabulum and multiple injuries was admitted. Right hip dislocation was treated with manual reduction. Left h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…The direction of the applied force and the local anatomy of the femur and acetabulum dictate the type of dislocation. If the applied force drives the hip into abduction and flexion, anterior femoral head dislocation occurs [2]. These forces may act from the knee up or along the inner thigh.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The direction of the applied force and the local anatomy of the femur and acetabulum dictate the type of dislocation. If the applied force drives the hip into abduction and flexion, anterior femoral head dislocation occurs [2]. These forces may act from the knee up or along the inner thigh.…”
Section: Discussionmentioning
confidence: 99%
“…Acquired unilateral posterior hip dislocation is typical of dashboard accidents and accounts for the vast majority of native hip injuries. Bilateral symmetric hip dislocations are exceedingly uncommon and are frequently accompanied by acetabular fractures [2]. It is imperative that a dislocated hip be reduced within 6 hours to prevent avascular necrosis of the hip [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 , 9 ] These special types of fractures are complex and the management option are extremely challenging,[ 10 ] as they can be associated to hip dislocation and/or other vital organs injury, even death, if excessive blood loss is involved. [ 1 , 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] These special types of fractures are complex and the management option are extremely challenging, [10] as they can be associated to hip dislocation and/or other vital organs injury, even death, if excessive blood loss is involved. [1,11] In this article, we present a case of post-traumatic bilateral traumatic acetabular fracture in a 48-year-old Bilateral acetabular fractures have long been described in seizure patients, osteoporotic acetabular insufficiency. Few cases have been reported in the context of high-velocity trauma.…”
mentioning
confidence: 99%
“…In practice, most hip fracture patients are aged and usually have underlying diseases and poor tolerance for anesthesia and surgery, and the cerebral vasoconstrictor anesthetic drugs will further increase their cerebrovascular resistance and lead to cerebral blood flow and metabolic rate decline [ 8 ], easily resulting in severe central nervous system (CNS) complications, so there is a close relationship between general anesthesia and cerebrovascular accidents. Some studies have confirmed that general anesthesia is a risk factor for the occurrence of cerebrovascular accidents [ 9 , 10 ], but no research has deeply explored the correlation of the occurrence of cerebrovascular accidents with general anesthesia, and the effects of factors such as blood pressure, age, and the amount of medications on the incidence of cerebrovascular accidents in hip fracture patients under general anesthesia remain unclear. Based on this, 240 hip fracture patients were selected for the study herein, with the results reported as follows.…”
Section: Introductionmentioning
confidence: 99%